Fecal microbiota transplantation—could stool donors’ and receptors’ diet be the key to future success? - Silva, Rita; Dinis, Liliana; Peris, Arnau; Novais, Luís; Calhau, Conceição; Pestana, Diogo; Marques, Cláudia (Frontiers in Gastroenterology, 2023)
Fecal microbiota transplantation (FMT) is indicated in many countries, for patients with multiple recurrences of Clostridioides difficile infection (CDI) who have failed appropriate antibiotic treatments. Donor selection is a demanding and rigorous process in view of the implementation of FMT programs worldwide. One of the most noteworthy factors that has been shown to affect FMT outcomes is the microbial diversity of the stool donor. Donor's microbiota detailed assessment is crucial, as the microbiota is complex, dynamic and resilient and a healthy microbiota has several dimensions in addition to the absence of pathogens. Diet is one of the most important factors that modulate the composition and function of the GM and have a critical role in orchestrating the host-microbiota crosstalk throughout life. The diversity of the human GM seems to be related to the variations in dietary patterns. Currently, the dietary pattern of stool donors and receptors is not taken in consideration in any orientation for FMT. Here we reflect about the importance of including this type of assessment in the stool donors screening process, knowing the impact of diet on the GM, as well as the importance of monitoring receptors' diet to favor the engraftment of the transplanted microbiota.